UNDERSTANDING DESIGN APPROACH FOR BILINGUAL ROADWAY DIRECTIONAL SIGN - Siahaan, Reynaldo; Jayme, Jamiel Louiee (Unika Santo Thomas, 2020)
The use of bilingual roadway directional sign is getting more important worldwide. It is triggered by the increasing concerns about the importance of providing the same information for foreigners as locals.Â However, while some countries have set their regulations and standards, there is still no general standard produced in the market about the adequate design for the bilingual roadway directional signs.Â This study explores available standards and discusses some issues concerned by comparing various bilingual directional signs practices in different countries and analyzing them based on related theories and past studies. Several similarities and consistencies were found in many countries, and thus particular guidance in the design approach for bilingual road directional sign is concluded. The design approach should pay attention to text volume, order, physical distinction, and also familiarity.